Electrothermal bipolar vessel sealing devices are associated with lower rates of postoperative complications compared to ultrasonic devices in vulvar cancer surgery - Milla K. Mörsky; Ilkka S. Kaartinen; Reita H. Nyberg (PLoS ONE, 2025)
Introduction Electrothermal bipolar vessel sealing devices (EBVS) and ultrasonic devices (US) – collectively known as advanced hemostasis devices (AHDs) – are considered equally feasible in laparoscopic procedures. However, US devices have been demonstrated to be more susceptible to abnormal heat accumulation when activation cycles are rapidly repeated, causing results from laparoscopic procedures to be poorly translated to vulvar cancer surgery. In this study, we aimed to determine whether EBVS and US are comparable in terms of peri- and postoperative morbidity in vulvar cancer surgery. Methods This retrospective single-center study comprised patients who underwent a primary vulvectomy, partial vulvectomy, or radical local resection with an AHD in Tampere University Hospital, Finland, in 2011–2023. Our primary outcome measure was the Clavien-Dindo grade, which measures the incidence and severity of postoperative complications in the early (30-day) postoperative period. Secondary outcome measures were blood loss, postoperative blood transfusions, operative time, the total volume of groin drain output, and length of hospital stay. Results Eighty-six patients were included (EBVS n = 45, US n = 41). Postoperative complications (Clavien-Dindo grades II – V) were significantly less common in the EBVS group compared to the US group (60% vs 85% in the EBVS and US groups, respectively; p = 0.015). The difference was driven by a discrepancy in grade II complications (49% vs 71%), which consisted primarily of infections in both groups. In a multivariable regression analysis adjusting for the extent of surgery, the use of an EBVS device was independently associated with a lower likelihood of postoperative complications compared to US (aOR 0.3, 95%CI 0.1–0.9 for EBVS vs US; p = 0.030). Both the amount of operative blood loss (median (IQR) 50 (45–200) ml vs 150 (88–400) ml; p = 0.005) and length of hospital stay (median (interquartile range) 6 (4–8) vs. 8 (6–10) days; p = 0.002) were lower in the EBVS group, but surgical device did not independently predict the highest quartile of either variable. The amount of postoperative blood transfusions, operative time, or groin drain output did not significantly differ between the groups. Conclusions The data from this study suggests electrothermal bipolar vessel sealing devices could reduce early postoperative complications, especially those related to the surgical site, in vulvar cancer surgery compared to ultrasonic devices. Prospective studies are needed to ensure the generalizability of the results.